Dataset on the effects of spermidine on linking number differences between histone H1-free and histone H1-bound circular polynucleosomes - Zhang, Hao (2018)
The data presented in this article are related to the research article entitled "Quantitative determination of linking number differences between circular polynucleosomes and histone H1-bound circular polynucleosomes" Zhang et al. (in press) [1]. DNA linking number differences between histone H1-free and histone H1-bound circular polynucleosomes at various spermidine concentrations was quantitatively determined by chloroquine-based gel electrophoretic analysis in this work, which provides information on the topological effects of histone H1 and spermidine on the linker DNA between nucleosomes.